2021
DOI: 10.20947/s0102-3098a0173
|View full text |Cite
|
Sign up to set email alerts
|

Prematuridade no Brasil entre 2012 e 2019: dados do Sistema de Informações sobre Nascidos Vivos

Abstract: O objetivo deste estudo é analisar a tendência de prematuridade no Brasil, entre 2012 e 2019, segundo características sociodemográficas, do pré-natal e parto. Trata-se de um estudo ecológico de série temporal, em que foram calculadas as proporções de prematuridade segundo as regiões do Brasil, idade materna, escolaridade materna, raça/cor, número de consultas pré-natal e tipo de parto, a partir dos dados do Sistema de Informações sobre Nascidos Vivos (Sinasc). Sequencialmente, foram aplicados modelos de regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 17 publications
2
15
1
22
Order By: Relevance
“…Taking into consideration the impact of prematurity on newborn morbidity and mortality, with possible permanent sequelae, and the high costs to the health system, information on its occurrence is essential for organizing health care, especially for the most vulnerable groups. In the study by Martinelli et al, 5 the proportion of prematurity in Brazil showed a decreasing trend from 2012 to 2019, with variations according to maternal characteristics. In view of the emergence of the COVID-19 pandemic as of 2020, the inadequate control policy and possible influence of the virus on the number of premature births, this study aimed to measure the prevalence of prematurity in Brazil, according to macro-region and maternal characteristics, over the past 11 years, and compare the proportions during the SARS-CoV-2 pandemic, 2020 and 2021, with those of the historical series from 2011 to 2019, pre-pandemic period.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Taking into consideration the impact of prematurity on newborn morbidity and mortality, with possible permanent sequelae, and the high costs to the health system, information on its occurrence is essential for organizing health care, especially for the most vulnerable groups. In the study by Martinelli et al, 5 the proportion of prematurity in Brazil showed a decreasing trend from 2012 to 2019, with variations according to maternal characteristics. In view of the emergence of the COVID-19 pandemic as of 2020, the inadequate control policy and possible influence of the virus on the number of premature births, this study aimed to measure the prevalence of prematurity in Brazil, according to macro-region and maternal characteristics, over the past 11 years, and compare the proportions during the SARS-CoV-2 pandemic, 2020 and 2021, with those of the historical series from 2011 to 2019, pre-pandemic period.…”
Section: Introductionmentioning
confidence: 91%
“…4 The analysis of the maternal characteristics of these records revealed a higher frequency in pregnant women at extremes of age (≥ 40 years; < 15 years), with fewer than seven prenatal care visits and less than eight years of schooling. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Still, our data shows a prematurity rate of 17.6%, higher than that of Brazilian population, assessed through the Information System on Live Births (Sinasc) between 2012 (10.87%) and 2019 (9.95%), which points out the importance of the developmental surveillance of these children. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Estudo que avalio a taxa de prematuridade no Brasil no período de 2012 a 2019, indicou tendência decrescente, especialmente no ano de 2015, cuja foi de 9,77%. A idade materna igual ou superior a 45 anos caracterizou-se como fator contrário a essa tendência, bem como a condição da mulher de ser indígena ou analfabeta (Martinelli, Dias, Leal, Belotti, Garcia & Santos Neto, 2021). Posteriormente a este período, a situação pandêmica decorrente da circulação do vírus SARS-CoV-2, indicou aumento dos casos de prematuridade em gestantes (Bhering, 2021).…”
Section: Introductionunclassified